Assessment of nutrient allocation and metabolic turnover rate in Pacific white shrimp Litopenaeus vannamei co-fed live macroalgae Ulva clathrata and inert feed: dual stable isotope analysis - Gamboa Delgado, Julián; Peña Rodríguez, Alberto; Ricque Marie, Denis; Cruz Suárez, Lucía Elizabeth (National Shellfisheries Association, 2011)
The present study quantified the relative contribution of dietary carbon and nitrogen supplied by live biomass of the green macroalgae Ulva clathrata and a commercial inert feed to the growth of juvenile shrimp Litopenaeus vannamei. The stable isotope ratios of carbon and nitrogen (δ13C and δ15N) were analyzed in both food sources, whole bodies and muscle tissue of shrimp reared on co-feeding regimes where 75, 50 and 25% of daily consumed macroalgal biomass was substituted by inert feed (regimes 75F/25U, 50F/50U and 25F/75U, respectively). Higher growth rates were observed in shrimps fed on regime 75F/25U (k = 0.062), followed by shrimps fed only inert feed (100F, k = 0.060). Animals reared only on U. clathrata (100U) showed minimal growth (k = 0.008) and very high metabolic turnover rates of carbon and nitrogen. Isotopic values measured in inert feed (δ13C= -23.0 ‰, δ15N= 9.7‰) and macroalgae (δ13C= -13.1‰, δ15N= -3.5‰) were very contrasting and both had a rapid influence on the isotopic values of shrimp. Animals reached full isotopic equilibrium through growth and fast metabolic turnover in only 2 weeks, except shrimps fed only macroalgae. At the end of the experiment, δ13C and δ15N values in shrimp reared on all co-feeding regimes were strongly biased towards the isotopic values of U. clathrata. Total dry matter contributions to growth were estimated using an isotope mixing model and considering the elemental concentration of both nutritional sources. Results indicated that shrimps in the co-feeding regimes incorporated significantly higher amounts of dietary carbon and nitrogen from the macroalgal biomass. Shrimps in treatment 75F/25U incorporated 52% of carbon from the inert feed and 48% from the macroalgae. Animals under feeding regimes 50F/50U and 25F/75U incorporated higher amounts of dietary carbon from U. clathrata (65-89%) when compared to carbon proportions supplied by both co-feeding regimes (33-70%) and also incorporated the majority of nitrogen from the macroalgae. However, a high incorporation of nitrogen was not reflected in high growth in the latter treatments as metabolic turnover rates were very high. Estimated turnover rates ranged from 0.049 to 0.191 d-1 for carbon and from 0.013 to 0.100 d-1 for nitrogen and values followed an increasing trend as a function of macroalgae consumption. Nitrogen half-times in tissue consistently decreased throughout the different treatments from 9.5 d (100F) to 6.4 d (100U). Proportions of incorporated nutrients in muscle tissue followed similar patterns as those observed in whole bodies.